College student engagement and success through inclusive learning environment and experiential learning in courses about Israel and Palestine - Zeedan, Rami (Frontiers in Education, 2024)
IntroductionThis study examines the impact of pedagogical redesign on two courses about Israel and Palestine, focusing on fostering an inclusive learning environment. The project aimed to address challenges such as student retention, attendance, participation, and academic performance by implementing innovative teaching strategies tailored to diverse student backgrounds.MethodsThe redesign incorporated several key interventions: an experiential learning-based final assignment, scaffolded into multiple steps with opportunities for feedback; group discussions to promote active learning and cooperation; and the integration of optional multimedia resources, such as YouTube videos and podcasts, to enhance engagement and time on task. Additionally, students were involved in the evaluation process by providing feedback and were offered the opportunity to publish their final projects on a public website, further incentivizing their work. To examine the effectiveness of these changes, the study employed a mixed-methods approach. This approach involved the collection and analysis of both quantitative data (such as surveys and performance metrics) and qualitative data (such as student feedback and one-way ANOVA analysis) across six undergraduate course offerings between 2019 and 2024.ResultsThe interventions were tested with students from varied backgrounds engaging in complex discussions. The initial findings revealed significant improvements in critical metrics, including reduced drop/fail/withdraw rates, increased time on task, and higher grades. Students demonstrated enhanced engagement and a more positive overall learning experience, indicating the potential for further positive outcomes.DiscussionThe preliminary results suggest that the implemented pedagogical changes effectively created a more inclusive and engaging learning environment. By integrating experiential learning, providing timely feedback, and utilizing diverse resources, the project demonstrated the potential for scalable improvements in student outcomes.